Más allá del inglés estandarizado: revisión de ingleses de países independientes del siglo XX (audiolibro). (2023)
With the purpose of teaching English from a phenomena-based learning theory, and contributing to making its development and influence visible from a decolonial perspective, this project of creation and interpretation under the line of research Representative and imaginary discourses in social educational action; through a historical investigation and artistic expression, aims to create an audiobook that allows us to know other faces beyond the imperial English. We compose the material to be developed based on 3 fundamental components: The historical-social component: It presents the history of the development of English from the perspectives of territories that, through processes of independence from the British Empire, have freed themselves from cultural subjugation but have adopted English as their official language since the decoloniality, diversifying the dialects of the language. The pedagogical component: It encourages a critical view of the cultural diversity that exists in English thanks to the use of phenomena as a part of Phenomena-based learning theory, combating the standard imagery of the language through activities and elements that stimulate the progress of students' language skills. The artistic component: It seeks to represent through visual and aesthetic elements, specifically artistic make-up captured in photographs, the diversity presented in the historical component, exposing its origin and cultural relevance, and giving a representation through cultural appreciation to the selected countries in the audiobook.